ANALISA PERBANDINGAN KONSUMSI BAHAN BAKAR DAN TENAGA YANG DIHASILKAN PADA TIAP PUTARAN MESIN DI MESIN TOYOTA K3-VE DENGAN METODE PEMBEBANAN TETAP MENGGUNAKAN DYNO TEST MAHA LPS 3000 - Widyartono, Andreas Edi; Kristianto, Stevanus Brian; Deprian, Lukyawan Pama (Technologic, 2019)
The consumption of fuel and power produced on an internal combustion engine is one factor to determine the efficiency of a machine. The small amount of fuel consumed will vary, among others, depending on the condition of the load, engine speed and construction of the engine itself. Fuel consumption is different at each engine speed to produce the same torque. In this study, the author will test a machine to prove fuel consumption through a graph of fuel consumption of power produced at each engine speed by using a Toyota Avanza car with a capacity of 1300 cc with a manual transmission as the object of research, a Dynotest Brand Chassis MAHA LPS 3000 made in Germany with a capacity of up to 450 BHP as a testing tool, as well as a Scan Tool as a measuring instrument related to fuel use. Tests will be carried out by giving varying loads to the engine with Dynotest, then measured fuel consumption indirectly through a Pulse Width Modulation signal that is read on each load. Calculations from the test results show that the Toyota Avanza engine with a capacity of 1300cc, shows that the most efficient use of fuel is at 3000 rpm to 4000 rpm.